Mesenchymal Stem Cells Ameliorate DSS-Induced Experimental Colitis by Modulating the Gut Microbiota and MUC-1 Pathway - Wang H; Sun Y; Xiao FJ; Zhao X; Zhang WY; Xia YJ; Wang LS (Dove Medical Press, 2023)
Han Wang,1,2,* Yang Sun,1,2,* Feng-Jun Xiao,3,* Xia Zhao,2,4 Wei-Yuan Zhang,1,2 Yu-Jun Xia,1 Li-Sheng Wang1,2 1School of Basic Medicine, Qingdao University, Qingdao, 266071, People's Republic of China; 2Laboratory of Molecular Diagnosis and Regenerative Medicine, The Affiliated Hospital of Qingdao University, Qingdao, 266000, People's Republic of China; 3Beijing Institute of Radiation Medicine, Beijing, 100850, People's Republic of China; 4Department of Hematology, The Affiliated Hospital of Qingdao University, Qingdao, 266000, People's Republic of China*These authors contributed equally to this workCorrespondence: Li-Sheng Wang, Laboratory of Molecular Diagnosis and Regenerative Medicine, The Affiliated Hospital of Qingdao University, Qingdao, 266000, People's Republic of China, Email lishengwang@qdu.edu.cn Yu-Jun Xia, School of Basic Medicine, Qingdao University, Qingdao, 266071, People's Republic of China, Email xiayujun62@163.comPurpose: Mesenchymal stem cells (MSCs) have become novel therapeutic agents for the treatment of inflammatory bowel diseases (IBDs). However, the precise cellular and molecular mechanisms by which MSCs restore intestinal tissue homeostasis and repair the epithelial barrier have not been well elucidated. This study aimed to investigate the therapeutic effects and possible mechanisms of human MSCs in the treatment of experimental colitis.Methods: We performed an integrative transcriptomic, proteomic, untargeted metabolomics, and gut microbiota analyses in a dextran sulfate sodium (DSS)-induced IBD mouse model. The cell viability of IEC-6 cells was determined by Cell Counting Kit-8 (CCK-8) assay. The expression of MUC-1 and ferroptosis-related genes were determined by immunohistochemical staining, Western blot, and real-time quantitative polymerase chain reaction (RT-qPCR).Results: Mice treated with MSCs showed notable amelioration in the severity of DSS-induced colitis, which was associated with reduced levels of proinflammatory cytokines and restoration of the lymphocyte subpopulation balance. Treatment with MSC restored the gut microbiota and altered their metabolites in DSS-induced IBD mice. The 16s rDNA sequencing showed that treatment with MSC modulated the composition of probiotics, including the upregulation of the contents of Firmicutes, Lactobacillus, Blautia, Clostridia, and Helicobacter bacteria in mouse colons. Protein proteomics and transcriptome analyses revealed that pathways related to cell immune responses, including inflammatory cytokines, were suppressed in the MSC group. The ferroptosis-related gene, MUC-1, was significantly upregulated in the MSC-treated group. MUC-1-inhibition experiments indicated that MUC-1 was essential for epithelial cell growth. Through overexpression of MUC-1, it showed that upregulation of SLC7A11 and GPX4, and downregulation of ACSL4 in erastin and RSL3-treated IEC-6 cells, respectively.Conclusion: This study described a mechanism by which treatment with MSCs ameliorated the severity of DSS-induced colitis by modulating the gut microbiota, immune response, and the MUC-1 pathway.Keywords: inflammatory bowel disease, mesenchymal stem cells, gut microbiota, MUC-1, multi-omics